Workplace Attachment among a sample of workers in SONELGAZ company (SDE) Constantine - Kaddour, Imed; Benabderrahmane, Tahar (Journal of Human Sciences, 2022)
The present study aimed to explore the level of Workplace Attachment and determine whether there are significant differences between(age - gender – years of service- educational level-job rank-family status) categories in Workplace Attachment levels .The research is based on descriptive approach. Questionnaire assessments,  using  the Adult Attachment Workplace scale (AAW), were collected from 79 workers in Sonelgaz company (SDE) Constantine.The findings showed  that the level of Workplace Attachment among participants is medium. No significant differences in Workplace Attachment due to the above-mentioned variables.